Estabilidade, avaliação clínica e microbiológica de dentifrício de própolis vermelha brasileira - Lotif, Mara Assef Leitão (2022)
Introduction: Bioactive molecules from natural products have been incorporated into dental formulations in order to prevent or treat oral diseases. A natural product of great interest to the pharmaceutical and dental industries is Brazilian red propolis (BRP), with its antiinflammatory and antimicrobial properties strongly documented in the literature. In toothpastes, the incorporation of propolis allows the release of the active in the oral environment daily. Objectives: To evaluate the in vitro stability and clinical efficacy of a dentifrice developed with 1% BRP extract in individuals undergoing orthodontic treatment. Material and Methods: This research was divided into two stages. The first stage aimed to evaluate the stability of different forms of fluoride in BRP toothpaste (patent number BR1020170110974) formulated with 1450 μg/g F-. Thus, total fluoride (TF), total soluble fluoride (TSF) and ionic fluoride (IF) were evaluated. For this, the potentiometer technique was used, with ion-specific electrode, where a total of 5 samples were analyzed, each one in duplicate and the equipment calibrated with standard solutions. They were evaluated at three different times: fresh samples, after 12 months and 24 months. The second stage was a randomized, double-blind clinical study. A total of 42 participants, aged between 12 and 18 years, with fixed orthodontic appliances, free from caries (ICDAS II= 0) and with good systemic health status, were randomized into 2 groups, G1 (BRP fluoride toothpaste) and G2 (common fluoride toothpaste). Subjects used the toothpaste for four weeks, where saliva was collected and the visible plaque index (VPI) was recorded during two periods, baseline (D0) and 4 weeks later (D28). For the microbiological analysis, two dilutions were established, and the colony forming units (CFU) of Lactobacillus spp. were identified and the values expressed as log (CFU/mL). Results: After 12 months the samples showed TF concentration ranging from 1198.9 ± 26.9 to 1443.6 ± 33.4 ppm F, TSF ranging from 869.6 ± 105.5 to 965.8 ± 149.8 ppm F and IF ranging from 223.5 ± 14.8 to 269.7 ± 10.1 ppm F. After After 24 months of aging, the samples showed TF concentration ranging from 763.5 ± 73.2 to 1083.1 ± 32.4 ppm F, TSF ranging from 552.3 ± 39.9 to 758.4 ± 141.1 ppm F and IF ranging from 102.2 ± 4.0 to 174.7 ± 4.9 ppm F. In the study clinically, the CFU counts found in G1 for the first dilution were 1.15 ± 0.41 at D0 and 0.68 ± 0.15 at D28 (p < 0.05) and for G2 it was 1.33 ± 0, 52 at D0 and 1.84 ± 0.39 at D28 (p < 0.05). For the second dilution, it was found for G1 0.87 ± 0.34 at D0 and 0.64 ± 0.37 at D28 (p < 0.05) and for G2 1.54 ± 0.47 at D0 and 1.62 ± 0.37 at D28 (p < 0.05). The corresponding VPI values for G1 and G2 were 38.10 ± 17.95 at D0 and 20.60 ± 16.44 at D28 (p < 0.05), and 38.38 ± 19.65 at D0 and 27, 40 ± 14.63 at D28 (p < 0.05), respectively. Conclusion: The fluoride values found in the fresh samples were as expected, but the concentration decreased with storage time. TSF values remained relatively stable only up to one year of aging. The BRP toothpaste showed antimicrobial activity against Lactobacillus spp. and decrease the VPI in up to 4 weeks of use. Encouraging results were found, but more clinical, randomized, controlled trials are needed to assess the long-term use of BRP toothpaste and its role in preventing dental caries and periodontal disease.